Budgeting Costs and Returns for Southwest Florida Citrus Production, 2003-04 - Ronald P. Muraro; Fritz M. Roka; Robert E. Rouse (EDIS)
Estimated costs and returns of growing processed-market round oranges and fresh-market seedless grapefruit in the Southwest area of Florida are presented for the eighth consecutive year. The format presented may be used by individual growers to budget costs and returns, utilizing individual data on specific groves. September 2004.